THE EFFECT OF THE APPLICATION OF VARIOUS CONCENTRATIONS OF ECOENZYME AND CUTTINGS SHAPE ON THE GROWTH OF ROSE PLANT STEM CUTTINGS (Rosa hybrid) - Muhammad Ainun Nafis; Agus Sugianto; Mahayu Woro Lestari (AGRONISMA, 2022)
Ecoenzyme is a type of liquid organic fertilizer made through fermentation of organic materials such as vegetable and fruit waste with sugar and water. Ecoenzyme has been pluralized as fertilizer for plants. The purpose of this study is for, 1.) Knowing the effect of ecoenzyme applications and various forms of cuttings on the growth of rose plant stem cuttings, 2.) Knowing the effect of ecoenzyme applications and various forms of cuttings on shoot / root ratio of rose plant stem cuttings, 3.) Know the optimum concentration of ecoenzyme to be applied to rose seedlings. This research was conducted in Tlogomas Village, Lowkwaru subdistrict, Malang City in February-July 2021. This study used the Experimental Method and Factorial Randomized Block Design (FRBD). The first factor is the concentration of ecoenzymes with 4 treatment levels, namely, 0 ml/L, 6 ml/L, 8 ml/L and 10 ml/L and the second factor is the shape of the cuttings with 3 treatment levels, namely, horizontal cut shape, oblique cut shape and the shape of a tapered cut. Observation parameters include: temperature, humidity, time of shoot emergence, shoot length, number of leaves, longest roots and shoot/root ratio. The results show 1.) There is an interaction between the treatment of various concentrations of ecoenzyme and various forms of cuttings on the observation variable when shoots appear. There was an interaction between the treatment of various concentrations of ecoenzymes with various forms of cuttings at the age of 14 and 21 DAP on the observation variable of shoot length, on the observation variable the number of leaves an interaction occurred at the age of 49, 56 and 63 DAP. While the longest root observation variable shows an independent effect and the shoot/root ratio observation variable does not show a significant effect. 2.) Ecoenzyme concentration of 10 ml/L significantly affected the growth of rose stem cuttings on the observed variables of shoot length, number of leaves and longest roots. 3.) The shape of the tapered cutting has a significant effect on the growth and yield of rose cuttings on the variables of shoot length, number of leaves and longest roots.